Structural basis of IRGB10 oligomerization by GTP hydrolysis - Ha, Hyun Ji; Kim, Ju Hyeong; Lee, Gwan Hee; Kim, Subin; Park, Hyun Ho (Frontiers in Immunology, 2023)
Immunity-related GTPase B10 (IRGB10) is a crucial member of the interferon (IFN)-inducible GTPases and plays a vital role in host defense mechanisms. Following infection, IRGB10 is induced by IFNs and functions by liberating pathogenic ligands to activate the inflammasome through direct disruption of the pathogen membrane. Despite extensive investigation into the significance of the cell-autonomous immune response, the precise molecular mechanism underlying IRGB10-mediated microbial membrane disruption remains elusive. Herein, we present two structures of different forms of IRGB10, the nucleotide-free and GppNHp-bound forms. Based on these structures, we identified that IRGB10 exists as a monomer in nucleotide-free and GTP binding states. Additionally, we identified that GTP hydrolysis is critical for dimer formation and further oligomerization of IRGB10. Building upon these observations, we propose a mechanistic model to elucidate the working mechanism of IRGB10 during pathogen membrane disruption.